Pengaruh Profesionalisme Auditor Dan Etika Profesi Auditor Terhadap Pertimbangan Tingkat Materialitas - Iriyadi, Iriyadi; Supriadi, Yoyon; Vannywati, Vannywati (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2011)
Professionalism became the main requirement for the person who worked as an auditor and a member of the Accountant Public Officer. Professional image of someone in the profession as an auditor on the basis of proficiency in planning, implementation and evaluation of the results of the examination procedure and sufficient confidence of knowledge and their responsibilities. Auditors who have high professional views will contribute to a credible by decision makers. Professional ethics is a set of principles or moral values that bind the community or someone who has been determined by a group or organization associated with the fro professional relationship. In performing its duties and obligations as an auditor must comply with the code of ethics that have been made by the Indonesian Institute of Accountants. Ethical principle of responsibility, public interest, integrity, objectivity, competence and professional prudence, confidentiality, professional behavior, and technical standards in the decision making process. Auditors regarding materiality considerations are considerations and influenced by perceptions of professional auditors to the needs of people who have adequate knowledge and that will put confidence in the financial statements. This study aims to determine the relationship of professionalism and professional ethics of auditors consideration of the level of materiality for financial reporting purposes auditorium. Data used in this study was obtained from questionnaires, completed by the respondents. Respondents in this study is an accountant who worked in public accounting firms in the Jakarta area. Statistical methods used to test the hypothesis is multiple regression. The results of this study indicate that the professionalism of auditors have the effect of 50.7% against the level of materiality considerations. Professional ethics for auditors to have 75% influence on the level of materiality considerations. And professionalism of auditors with the auditors professional ethics at the same time has the effect of 77.3% against the level of materiality considerations.